A Highly Abundant Lectin Protein in Arabidopsis thaliana Confers Resistance Against Pathogens - Omega, Maria Prihtamala; Thomas-Hall, Skye; Schenk, Peer; Kobe, Bostjan (Annales Bogorienses, 2008)
Lectins are glycoproteins that recognize and bind to specific carbohydrates. They are involved in a range of biological functions, such as plant defence, storage proteins seed germination, and plant microbe interactions. Lectin 3.1 (At3g15356) is a protein in plant model, Arabidopsis thaliana, that has been shown to be up-regulated in all defence pathways especially in response to methyl ester jasmonale (MJ). All that was known about the gene was that it had go d homology to the beta domain of legume lectins. That aim of this project was to characterize the structure and function of the lectin protein using CD spectra and X-ray crystallography. AT-DNA insertion line for the lectin gene and a number of 35S over-expression line that had varying levels of expression had been generated, but none of these showed any obvious phenotype. Two protein bands were observed on comassie stained SDS-PAGE gels in the over-expression lines and in MJ induced wild-type (WT). The two protein bands represented two isoforms of the lectin 3.1 protein; in a glycosylation assay the larger protein band was shown to be heavily glycosylated. A nematode (M. incognita) disease assay discovered that the lectin overexpression lines had les nematode eggs compared to that of the WT and that the insertion line bad more nematode eggs than the WT. This data provide evidence that lectin 3.1 improves plant resistance against M. incognita infection. interestingly, the nematode gut lining contains fucose with which lectin 3.1 binds to.